2005
DOI: 10.1002/jclp.20218
|View full text |Cite
|
Sign up to set email alerts
|

Clinician to frontline soldier: A look at the roles and challenges of army clinical psychologists in Iraq

Abstract: Psychologists have a long and respected history of service during wartime that dates back to World War I. From the early days of scientific personnel selection, clinical psychologists have made a number of wartime contributions. Today, Army clinical psychologists serving in Iraq are providing behavioral health services as both clinicians and prevention specialists in order to meet the psychological and emotional needs of service members abroad. They are also performing as Army officers and soldiers contributin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Johnson et al (2005) identified several distinctive features of practicing in an embedded environment. In addition to the blended roles of officer and clinical psychologist, the UCP cannot necessarily choose to enter or exit clinical relationships (see also Moore & Reger, 2006). The UCP will have unavoidable close personal contact with patients.…”
Section: Multiple Relationshipsmentioning
confidence: 96%
“…Johnson et al (2005) identified several distinctive features of practicing in an embedded environment. In addition to the blended roles of officer and clinical psychologist, the UCP cannot necessarily choose to enter or exit clinical relationships (see also Moore & Reger, 2006). The UCP will have unavoidable close personal contact with patients.…”
Section: Multiple Relationshipsmentioning
confidence: 96%
“…U.S. Army chaplains are first trained as chaplains and then, sometimes years into their career, may receive specialized training in marriage and family therapy. Chaplains may identify themselves first as a chaplain, then a soldier and military officer, and last as a therapist, which is much in the same way that military psychologists identify themselves as a soldier over therapist (Moore & Reger, 2006). Chaplains may consider therapy to be only a small piece of their work as a chaplain and it may be important to discuss their identity formation in supervision.…”
Section: Critical Areas Of Supervisory Competencementioning
confidence: 98%
“…They are instructed to always hold the military as a "pseudo-client" in the room with the soldier. Consequently, studies of clinical military psychologists have shown that these psychologists struggle with meeting the needs of the Army as well as meeting the needs of their soldier-clients (Budd & Kennedy, 2006;Moore & Reger, 2006). Military mental health providers must continually assess soldiers' fitness for duty as they treat their soldier-clients' presenting issues.…”
Section: Critical Areas Of Supervisory Competencementioning
confidence: 98%
“…As such, while the work of the MMHP fulfils a number of roles, it tends to follow a set of principles devised during World War 1, which are known as the 7R's (Recognition, Respite, Rest, Recall, Reassurance, Rehabilitation and Return to Duty) and PIES (Proximity, Immediacy, Expectancy and Simplicity) (Palmer 2003). Thus, as outlined by Moore and Reger (2006), the broad aims are to deliver mental healthcare services as close to soldiers' units as possible; interventions are provided within as short a period a time as can be achieved; a treatment expectation of recovery is espoused; and mental healthcare services are kept simple and clear.…”
Section: Introductionmentioning
confidence: 98%
“…The MMHPs furthermore encountered variable levels of acceptance from commanding officers. Two US Army MMHPs reported on their experiences in the current Iraq conflict and highlighted, amongst many points, issues such as role conflicts, boundary violations, disagreements with commanding officers over the welfare of soldiers and administrative versus clinical responses to soldiers' behavioural and emotional difficulties (Moore and Reger 2006). Furthermore, in a report by two US MMHPs associated with the Persian Gulf War of 1991, it was recommended that MMHPs achieve more effective outcomes when embedded and closely identified with the deploying force (Engel and Campbell 1993).…”
Section: Introductionmentioning
confidence: 99%